The rainbow comes and goes : a mother and son on life, love, and loss - Cooper, Anderson; Vanderbilt, Gloria, 1924- (New York : Harper, 2016)
"A charming, intimate and fascinating collection of correspondence between broadcaster and #1 New York Times bestselling author Anderson Cooper and his mother, the celebrated Gloria Vanderbilt"--
Keywords: Cooper, Anderson; Cooper, Anderson -- Correspondence; Vanderbilt, Gloria, -- 1924-; Vanderbilt, Gloria, -- 1924- -- Correspondence; Cooper, Anderson; Vanderbilt, Gloria, -- 1924-; Television journalists -- United States -- Biography; Celebrities -- United States -- Biography; Mothers and sons -- United States -- Correspondence; BIOGRAPHY & AUTOBIOGRAPHY / Editors, Journalists, Publishers; FAMILY & RELATIONSHIPS / General; Celebrities; Mothers and sons; Television journalists; United States; Biography; Records and correspondence; Autobiographies; Personal correspondence